Identification of the appropriate fixation site to avoid peritoneal catheter migration based on a mechanical analysis. (1st January 2017) - Wang, Yujuan; Zou, Yao; Chen, Xinghua; Zhu, Jili; Xiang, Cuizhi; Jia, Houjun; Ding, Guohua; Wang, Huiming
Abstract: Aim: To conduct mechanical analysis on the relationship between abdominal wall fixation point and the displacement of catheter top, and establish the finite element model for the complex forces and conditions that the catheter wears in human abdominal cavity, in order to provide the scientific basis for optimizing the catheter position in abdominal wall fixation method. Methods: Using the PIPE59 finite elements to divide units, and taking the lower part of catheter, that is, below interior polyester cuff to simulate and compute the displacement formula. Results: The whole model includes a total of 1701 units. Periodic load was used to simulate the dynamic pressure that peritoneal dialysis catheter gets in abdominal cavity. The load direction was perpendicular to the catheter axis. We used pressure amplitude, duration and frequency as the boundary conditions, and adjusted the fixation point of the catheter lower part at the same time, thus calculating the extreme displacement value of the catheter top end with changing parameter conditions. We also did fitted regression on the results and obtained the displacement formula: y  = 0.2 × 0.87 x (y: the end displacement of peritoneal dialysis catheter, x: the distance between fixation point and the interior polyester cuff), R 2 : .982. Simulation the catheter maximal displacement on flat surface demonstrated that additional catheter fixation at the site of 9 cm or more below the internal cuff significantly restricted the catheter migration. Conclusions: The optimal position of fixation point in peritoneal dialysis is about 9 cm away from the interior polyester cuff.